Amitsur's theorem, semicentral idempotents, and additively idempotent semirings - Rachev Martin; Trendafilov Ivan (Open Mathematics, 2024)
The article explores research findings akin to Amitsur’s theorem, asserting that any derivation within a matrix ring can be expressed as the sum of an inner derivation and a hereditary derivation. In most results related to rings and semirings, Birkenmeier’s semicentral idempotents play a crucial role. This article is intended for PhD students, postdocs, and researchers.